Electrodeposition of nanostructured TiO2 thin film as an efficient bifunctional layer for perovskite solar cells. (1st February 2019) - Anuratha, Krishnan Shanmugam; Peng, Hsiao-Shan; Xiao, Yaoming; Su, Tzu-Sen; Wei, Tzu-Chien; Lin, Jeng-Yu
Abstract: In this current work, a bifunctional TiO2 thin film with reduced pin-hole effect and enhanced light trapping capability was successfully fabricated by using a facile galvanostatic anodic deposition route in the presence of Brij-58 soft template (ST). The surface morphology of electrodeposited TiO2 thin film using ST confirmed the formation of nano-sized TiO2 particles with improved porous nature than that of TiO2 thin film electrodeposited in the absence of ST. Compared with the conventional scaffold porous layer (PL) fabricated from commercial mesoporous TiO2 composed of ∼30 nm nanoparticles, the electrodeposited TiO2 film using ST demonstrated the reduced pinhole effect and improved light trapping feature. Owing to the bifunctional behavior of electrodeposited TiO2 using ST, the cell efficiency of the perovskite solar cell was achieved up to 17.06% which was ca.10% higher than those with commercial TiO2 nanoparticles.